GLOBALIZATION AND ITS RELATIONSHIP TO THE LEVEL OF CULTURAL AWARENESS OF BIOLOGY TEACHERS IN ALQADISIYAH GOVERNORATE - Firas ayal mate, Dr.prof.qahtan fadhil rahi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to identify globalization and its relationship with the level of cultural awareness of biology teachers in AlQadisiyah governorate, to achieve the research aims, the researchers used the descriptive analytical approach, the research sample consisted of (200) male and female teachers distributed on (4) schools in education directorates in AlQadisiyah governorate. The researchers built a scale of globalization and a scale of cultural awareness to be a research tools, the research reached the following results: - The presence of statistically significant differences at a significance level (0.05) in favor of the mean of biology teachers ’grades in the globalization scale. - The presence of statistically significant differences at the level of significance (0.05) in favor of the arithmetic mean of biology teachers ’grades in the cultural awareness scale. - There is a high correlation between the globalization scale and the cultural awareness scale. In light of this, researchers came out with a number of recommendations and proposals.